A grounded theory systematic review of environmental education for secondary students in the United States. Issue 3 (3rd July 2021) - Bowers, Alison W.; Creamer, Elizabeth G.
Abstract: Our world faces a range of environmental problems directly linked to or exacerbated by human actions and choices. Environmental education (EE) is one tool that can create a more environmentally literate citizenry. EE research contains numerous studies examining whether or not EE programs are achieving certain outcomes, yet research on the identification of important program factors remains unclear. The purpose of this grounded theory systematic review was initial exploration into what makes EE effective with secondary students. This research was designed to develop a grounded theory model that synthesizes the strategies and outcomes associated with EE for this specific context. A systematic search identified 39 studies published between 2011 and 2018 that examined EE for secondary students in the US. Grounded theory coding and theoretical sampling informed the development of the Implementation of Authentic Environmental Education Programs (IAEEP) model, which posits program authenticity as the core category underlying the process of EE with secondary students in the US. The resultant grounded theory model can help guide secondary school educators and EE practitioners in the development and implementation of EE for secondary students.